Preparation of Visible-light Responsive Rutile-TiO2(110) Wafer with Well-defined Surface by Chromium and Antimony Codoping - Kitta, Mitsunori; Onishi, Hiroshi (E-journal of surface science and nanotechnology, 2019)
Transition-metal doping for titanium dioxide (TiO2) is attracting attention for the study of visible-light responsive photocatalyst. Its photocatalytic properties were investigated via various spectroscopic approaches, though surface studies had not yet progressed owing to the difficulty in obtaining its well-defined surface. In this report, we propose that a well-defined crystalline TiO2(110) surface may be obtained by the codoping of chromium (Cr) and antimony (Sb) with commercially available wafers. Cr and Sb are codoped by a solid-state reaction of TiO2(110) wafer and dopant powder. The prepared wafer exhibited visible-light responsivity on absorption below wavelengths of 600 nm. The surface morphology characterization, performed by atomic force microscopy (AFM) revealed that the Cr and Sb codoped TiO2(110) surface has a well crystallized step-terrace structure that is atomically flat, while monodoped TiO2(110) surface does not. The codoping of Cr and Sb with TiO2(110) wafer should contributes towards retaining the stable rutile-TiO2 lattice structure and produces a well-defined TiO2(110) surface structure with visible-light responsive characteristics.